A freestanding carbon submicro fiber sponge as high-efficient bioelectrochemical anode for wastewater energy recovery and treatment. (1st January 2021) - Xu, Ting; Song, Jianan; Lin, Weichen; Fu, Boya; Guo, Xingguo; Huang, Xia; Wu, Hui; Zhang, Xiaoyuan
Graphical abstract: Highlights: Carbon fiber sponge MFC generates excellent current from wastewater. The linkage mechanism of electricity generation and COD removal is studied. Carbon fiber sponge exhibits remarkable stability under the operation for 2 years. Carbon fiber sponge enhances electrochemical microbial adhesion. Carbon fiber sponge has high electrochemical activity and low internal resistance. Abstract: Microbial fuel cells (MFCs), as a typical kind of microbial electrochemical technologies (METs), can achieve energy recovery and wastewater treatment. Microbial adhesion on electrodes directly affects microbe-electrode interactions, determining the performance of electricity generation and organic degradation. The anode with suitable structure and operation mode can reduce the limitation of fiber diameter-structure-interface trade-off to enhance microbe-electrode interaction. Here, we fabricated a carbon submicro fiber sponge with fiber diameter close to the size of electrogenic microorganism and operated it in filtration mode to greatly improve energy conversion. The carbon submicro fiber sponge exhibits a superior current yield of 17.4 A m −2 in the polarization curve with high electrochemical activity in MFC, which is 74% higher than that of the commonly used carbon fiber cloth anode. A higher chemical oxygen demand removal rate of 2.9 kg m −3 d − 1 is obtained with this novel anode (1.3-fold that of the benchmark). The linkage mechanism of electricity generation and organic degradation is analyzed. Moreover, a long-term stability is demonstrated with excellent current production after the operation over 2 years. Our results indicate that this carbon fiber sponge has remarkable application potential in microbial electrochemical technologies for energy recovery from wastewater.